Variations in climate drive behavior and survival of small desert tortoises - Berry, Kristin H.; Mack, Jeremy S.; Anderson, Kemp M. (Frontiers in Ecology and Evolution, 2023)
In the Mojave Desert, timing and amounts of precipitation profoundly affect availability of water and annual plant foods necessary for the threatened Agassiz's desert tortoise (Gopherus agassizii) to survive, especially during prolonged droughts. As part of recovery actions to increase declining populations, we translocated 83 juvenile and young desert tortoises raised in head-start pens for 4-10 years to a new location 15 km away during fall of 2013 and 2014. We tracked them for 9 years during a megadrought, during multiple years of low rainfall and a few years when precipitation neared or exceeded long-term norms. We evaluated behaviors and how precipitation and forage availability affected survival. At the end of the study, 21.6% of tortoises were alive and 6 had grown to adulthood. Annual models of survival indicated that tortoise size was the driving variable in most years, followed by number of repeatedly used burrows during periods of temperature extremes. Other variables affecting survival in ≥1 year were vegetation, movements during the first 2 years post-translocation, and condition index, a measure of health. Tortoises moved more, expanded home ranges, and grew rapidly in years when winter rainfall approached or exceeded long-term norms and annual plants were available to eat. During dry years, movements and growth were limited. Exceptions to this pattern occurred in the last year of study, a dry year: tortoises grew, moved more, and home ranges increased. The increase in size and approaching adulthood may have stimulated greater travelling. Some left the study area, indicating a need for large release areas. We may have aided survival by offering water twice yearly when handling, because some tortoise drank and increased in mass up to 40%. Prolonged droughts and hotter temperatures can limit recovery of populations, reduce survival of young tortoises, and increase the time to maturity.